KEDUDUKAN PARTAI POLITIK DALAM MENERIMA BANTUAN KEUANGAN PARPOL - Iqbal, Mohamad (Katalogis, 2016)
A democratic country that is based on the law, there is the protection of the human rights of its citizens. One of the rights that should be guaranteed by a State is the right of freedom of association, assembly and expression, as stated in its constitution, namely the Constitution of the Republic of Indonesia Year 1945. It can be seen in the provisions of Article 28 and 28E (3) UUDNRI 1945, concerning freedom of association and assembly, issued thoughts with oral and written, and so on are set by the Act and the provisions of Law No. 2 year 2011 concerning amendments to Act No. 2 of 2008 on Political Parties. With these freedoms, the government should be fair to the political parties that did not get state financial aid granted proportionally, while financial aid is only given to the political parties which have gained seats in the Parliament. Which cause many problems, whether financial aid political parties which have gained seats in the Parliament and the Council under the provisions of Law No. 2 of 2011 on political parties reflects the principle of popular sovereignty with justice. Corresponding problems mentioned above, this thesis is a normative study described prescriptive. Importance given financial aid to political parties, to strengthen the implementation of democracy and party system that is effective in accordance with the mandate of the Constitution of the Republic of Indonesia Year 1945 and the formation of political parties and the democratic process in the form of grants aim to recruit and retain the power to implement / realizing programs compiled with a particular ideology. In addition, provision must also reflect the principle of popular sovereignty with justice.